TITER ANTIBODY IgM DAN IgG PADA DONOR PLASMA KONVALESEN - resmi resmi aini (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2022)
ABSTRACT Convalescent plasma is plasma containing Covid-19 antibodies originating from patients who have recovered from Covid-19 disease which can help increase antibodies and reduce the amount of virus (Covid-19 antigen) in Covid-19 sufferers. Convalescent plasma contains a lot of factor VIII, leukocytes, platelets, polyclonal antibodies and anti-SARS-CoV-2 and as a therapy for COVID-19 patients. This study aims to determine the convalescent plasma in UDD PMI DKI Jakarta that meets the requirements for quality control of IgM and IgG titers with negative IgM and positive IgG results. This research is a descriptive analytic study. Data collection was obtained from the results of the rapid test of IgM and IgG of convalescent plasma donors in June 2021, totaling 945 samples. Data were analyzed univariately and presented in tabular form, then narrated. The results showed that there were 669 people (70.42%) who met the quality control requirements for IgM and IgG with negative IgM and positive IgG results. There were 275 people (29.10%) with negative IgM and negative IgG results and there was 1 person (0.11%) with positive IgM and positive IgG results who did not meet the requirements. Keywords: Covid-19, IgM and IgG titers, convalescent plasm